Intimal lesion of the primitive carotid due to blunt neck trauma - Peyroulou, Alfredo J.; Bergalli, Luis E.; Montandón, Pablo; Correa, Waldemar; Antúnez, Carlos; García Podestá, Pablo (Cirugía del Uruguay, 1982)
The authors present one case of a 32 year old patient who suffered blunt trauma in the neck, with an intimal tear of the primitive carotid, clinically and radiologically diagnosed in the pre operative. A surgical solution of the case is presented. lnternational statistical data is provided, and the authors conclude that the sugpicion of carotid lesion must arise in all cases of cervical trauma; that an urgent arteriography must be performed to confirm the lesion and that once the lesion is confirmed it must be operated on inmediately.